STRATEGI KULTURAL KELUARGA BALI DALAM MENJAGA BUDAYA RITUS DI KOMUNITAS TRANSMIGRAN - Septiana, Wayan; Gusti, Ririn; Putra, Ari (Comm-Edu (Community Education Journal), 2025)
This  study  examines  the cultural  strategies  of  Balinese  families  in  maintaining  cultural  rites  in transmigrant communities, especially in Kayu Negehri Village, Lampung Province. The research method uses a qualitative descriptive approach. The results of the study indicate that the strategies of Balinese families in maintaining cultural rites are carried out informally through daily practices such as praying together, ngayah, and making banten. These strategies include early enculturation, strengthening communication of the meaning of the rites, and collaboration with the indigenous community. Parents not only develop skills, but also shape children's understanding and emotional continuity of cultural values. The inheritance process takes place through habituation, role models, and contextual meaning of each cultural activity. This study emphasizes the importance of family education as a cultural strategy in maintaining Balinese rites amidst the challenges of global culture and multicultural life.